Advancing Green Nanotechnology: Harnessing the Bio-reducing Properties of Musa paradisiaca Peel Extract for Sustainable Synthesis of Iron Oxide Nanoparticles - Esther Uwidia Ikhuoria; Ita Erebho Uwidia; Rachel Obhade Okojie; Ikhazuagbe Hilary Ifijen; Ikechukwu Dorris Chikaodili; Awalul Fatiqin (Journal of Multidisciplinary Applied Natural Science, 2024)
A green synthesis method utilizing Musa paradisiaca peel extract as a reducing and stabilizing agent was employed to produce iron oxide nanoparticles. The synthesized nanoparticles were extensively characterized using FTIR, XRD, DLS, SEM, EDX, and TEM techniques. FTIR analysis confirmed the presence of iron metal and functional groups derived from the peel extract. XRD results indicated the presence of magnetite (Fe3O4) and/or maghemite (γ-Fe2O3) phases, signifying a high degree of crystallinity. DLS analysis provided valuable insights into the size distribution and polydispersity of the nanoparticles, revealing an average particle diameter of 43.35 nm and a polydispersity index of 0.612. SEM examination uncovered the presence of aggregated formations, where irregularly shaped nanoparticles exhibited either close packing or loose association, resulting in the formation of larger aggregates. These environmentally friendly iron oxide nanoparticles could potentially hold great promise for a variety of biological applications, including the potential for drug delivery and antimicrobial applications.